Clinical Profile of Injuries due to Paragliding Accident Attended in a Tertiary Hospital of Western Region of Nepal - Kandel, Ishwar Sharma; Acharya, K; Gupta, S; Shrestha, B; Bista, KB; Dhakal, RM; Tripathi, N (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Paragliding is an adventurous aerial sport which is performed regularly in and around Pokhara. The Western Region of Nepal (Especially Pokhara, Parbat, Baglung and Syanjya) is famous not only for its natural beauty but for adventurous sports like paragliding, ultraflight and bungee jumping etc. The growing popularity of paragliding sport has led to a steady increase in the number of associated injuries.Objectives: The main objective of this retrospective review is to find out characteristic of injuries in different of paragliding accidents.Methods: This is a retrospective review of paragliding injury cases who attended emmergency department of Gandaki Medical College, Pokhara, Nepal from June 2009 to May 2016. Demographic profile (Age, sex, address), type of flight, timing of accident, severity and pattern of injures were collected and analyzed using the frequency table.Results: Among 60 people who faced accidents and brought to hospital, four of them with severe multiple trauma were declared dead in the emergency department at the time of arrival. Fifty six patients were injured with varieties of injury. Among 56 survived patients, 14 (25%) were minor injuries and discharged from the Emergency Department after treatment for soft tissue trauma like abrasion or sprain. Twelve patients with polytrauma (Including four chest injury, two abdominal injury with multiple bone fractures) and rest of the patients were admitted and treated/reffered/discharged.Conclusion: Lower limb especially foot and ankle injury were the commonest type of injury followed by spine fracture in paragliding accidents.